2011
DOI: 10.3109/09513590.2011.569603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pelvic floor muscle strength between women undergoing vaginal delivery, cesarean section, and nulliparae using a perineometer and digital palpation

Abstract: A lower PFM strength was observed in women with a history of vaginal delivery compared to those undergoing cesarean section. Non-white race/ethnicity negatively affected PFM strength. Our data suggest that vaginal digital palpation may be used in clinical practice because of its expressive correlation with use of a perineometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
15
1
4
Order By: Relevance
“…Although some authors suggest that age and skin color are related to lower PFMS after childbirth 19 , in the current survey, a significant difference in PFMS was identified only in relation to education level. Primiparous women over 12 years of education and normal birth showed a significantly higher PFMS value.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Although some authors suggest that age and skin color are related to lower PFMS after childbirth 19 , in the current survey, a significant difference in PFMS was identified only in relation to education level. Primiparous women over 12 years of education and normal birth showed a significantly higher PFMS value.…”
Section: Discussioncontrasting
confidence: 92%
“…However, the authors suggest that the level of education may be associated with other factors such as socioeconomic condition, i.e. higher education, in general, is related to increased socioeconomic condition which in turn allows access to better nutrition, physical activity, and greater access to health care among others 19 . However, the socio-economic condition was not addressed in the current research, preventing more comparisons.…”
Section: Discussionmentioning
confidence: 79%
“…Vaginal delivery is associated with an increased rate of avulsion of puborectalis component of the levator ani muscle, and the use of forceps or vacuum also increases the damage7-8. A lower pelvic floor muscle strength was observed in women with a history of vaginal delivery compared to those undergoing Cesarean section9-10. In addition, recent studies showed that childbirth-related trauma may involve not only the levator ani muscle but also damage to fascia and connective tissue11-12.…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo no qual se analisou a correlação entre as medidas de força muscular, realizadas por meio da palpação vaginal digital e pelo perineômetro, concluiu que a palpação vaginal é importante para ensinar a contração correta dos MAP, mas não é um método com boa reprodutividade 28 . Outros autores, no entanto, mostraram resultados semelhantes aos do presente estudo 6,13,29,30 . Assim, acredita-se que a palpação vaginal digital possa ser usada na prática clínica para medir a força dos MAP, uma vez que a maioria dos estudos mostrou boa correlação com o perineômetro.…”
Section: Discussionunclassified
“…O parto vaginal é um dos fatores de risco para essa desnervação porque, durante o segundo estágio do trabalho de parto, a cabeça fetal pode provocar compressão e alongamento do nervo pudendo, causando estiramento dos tecidos e ligamentos da pelve 3,4 . Outros estudos demonstraram que o parto vaginal pode diminuir a força muscular do assoalho pélvico de mulheres primíparas e multíparas, quando comparadas com mulheres submetidas à cesárea e nulíparas [4][5][6] . A incontinência urinária é descrita como a disfunção do assoalho pélvico mais prevalente, afetando 34 a 38% de primíparas e multíparas três meses após o parto 7 .…”
Section: Introductionunclassified